Synthesis and fourier transform infrared spectroscopic studies of C-O bond in the Nickel(II) benzoate derivatives substitued with electron-attracting groups / Zuraida Khusaimi and Azlin Sanusi - Khusaimi, Zuraida; Sanusi, Azlin (2003)
Miniaturization of electronic devices increases the reliability and energy saving nature of electronic devices [8]. For the last 10 years or so scientists like Tour and Reed [5] has been enthusiastically studying, synthesizing and isolating molecules exhibiting conductive, semi-conductive and super-conductive ability. One of the major advantage in the manufacturing of molecular electronics is that they are self-assembled, by simply putting the right ingredients into a beaker, unlike time consuming microchip-producing technique. Computing speed can also be revolutionized to millions of times faster than of silicon material [5]. Nickel(II) benzoate is a metallomesogens, a potential low-dimensional electronic material. Its structure is assumed to follow the ligand-field theory [12].